Inventory Control Management System - PhakLen, Ehkan (2001)
This project is aimed at developing an inventory control management system to allow the operator controlling and updating the flow of inventory in any organization. This system is developed by using software Visual Basic version 6.0 integated with Microsoft Access 2000 and Seagate Crystal Report version 6.0. The Crystal Seagate Report is chosen because it is easy to developed and also its format more systematic compared to other report Format. Overall the developed system is increase the user's confidence because it is easy to used. Further works such as to upload the system to the Internet could be performed to improve the performance of the system.